Analysis and Optimization of Operational and Pollutant Attributes of Diesel Engine with CNT-Infused Orange Peel Biodiesel-Diesel Blend Fuel - Rai R.; Sahoo R.R. (My University, 2025)
The current study is performed to find sustainable solutions for the future of transportation and environmental well-being. Both conventional methods and experimental design table (L16 Orthogonal Array) techniques have been employed to examine and optimize a diesel-powered engine’s operational and pollutant parameters. The L16 Orthogonal Array is obtained through Taguchi’s experimental design approach using Minitab 16 software. The experimental design incorporated three control variables, namely engine speed, fuel type, and engine load, each with four levels. The operational parameters, namely brake thermal efficiency (BTE) and brake specific fuel consumption (BSFC), as well as the emission characteristics, including hydrocarbon (HC), carbon monoxide (CO), nitrogen oxide (NO), and smoke emissions, were acquired using the L16 orthogonal array (OA) and subsequently examined. The utilization of methodologies such as signal-to-noise (S/N) ratio and grey analysis was employed to determine the optimal operational state of the engine to achieve maximum performance while minimizing emissions. The engine’s ideal state of operation, in terms of BTE and BSFC, was determined to be at 75% engine load, 1000 r/min engine speed, and using 10−4 (in vol) carbon nanotube incorporated 20% orange peel biodiesel (OPB20CNT100) blended fuel (A3-B1-C4). The study indicated that engine load significantly influenced BTE and BSFC, with 84.05% and 87.79% contribution factors, respectively. At 25% engine load, 1000 r/min, and OPB20CNT100 fuel (A1-B1-C4) CO, smoke, NO, and HC emissions were the lowest. Engine load affects emissions the most. Engine BSFC increased 3.10% and NO emissions 1.77%. BTE, CO, smoke, and HC emissions decreased by 1.9%, 12.29%, 47.05%, and 47.22%, respectively, at optimal operating conditions concerning diesel fuel. This study shows that Taguchi-Grey’s experimental design optimizes diesel engine operational and pollutant attributes. The outcomes revealed that orange peel biodiesel infused with CNT can replace diesel fuel in an environmentally friendly way. This alternative fuel could clean and improve transportation. © Science Press, Institute of Engineering Thermophysics, CAS and Springer-Verlag GmbH Germany, part of Springer Nature 2024.